THE INFLUENCE OF USING SOCIAL MEDIA INSTAGRAM @KACAMATA_TULUNGAGUNG ON FULFILLING INFORMATION NEEDS (SURVEY ON INSTAGRAM FOLLOWERS @KACAMATA_TULUNGAGUNG) - Febriana, Fika; Aji, Gilang Gusti (The Commercium, 2023)
The development of times and technology has caused changes in the way humans communicate. If in the past the audience used conventional mass media; such as, newspapers, radio and television, now it is starting to experience a shift by utilizing internet-based digital tools in order to obtain information. Furthermore, digital-based media has various forms, one of which is social media Instagram, which is now starting to be used as a medium for disseminating information. In rural areas; such as, districts, the role of local Instagram social media is needed by the community in order to fulfill their information needs. The aim of this study is that to determine the effect of the use of social media @Kacamata_Tulungagung on fulfilling the information needs of its followers. Moreover, this study used descriptive quantitative research which used a series of influence and relationship analysis techniques. Based on the study it shows that the use of social media Instagram @Kacamata_Tulungagung has a significant effect on fulfilling the information needs of followers.